The Impact of the Role of Teacher and Balance of Power in Transforming Conventional Teaching to Learner-Centered Teaching in Malaysian Institution of Higher Education - Yap, W. L.; Neo, M.; Neo, T. K. (Universiti Putra Malaysia Press, 2016)
There have been many efforts in Malaysian institutions of higher education to move from curriculum-based education to outcome-based education. However, the readiness and acceptance level of teaching with ICT in Malaysian education is also still a challenge, and the confidence in developing effective learning materials and implementing more learner-centred teaching environments is still lacking. Due to this, there is an urge to investigate and propose guidelines for educators teaching in Malaysian institutions of higher education in order to have an easier transition from conventional teaching to a more learner-centred teaching environment. Weimer (2002) proposed five key strategies of learner-centred teaching to be incorporated into the instructional process, four of which were investigated. This research investigates the influence of implementing Weimer’s key changes in three learning environments (face-to-face teaching with PowerPoint, learning with multimedia application and online learning with multimedia application) on students’ learning outcomes. Data from pre- and post-tests, survey questionnaires and students’ comments were triangulated and ANOVA analyses were performed. The results indicate that students showed better appreciation of the balance of power given in the class and they accepted the change of the role of lecturer to a facilitator. The changes have resulted in better learner understanding and learner motivation. The positive results contributed in the form of a framework for tertiary education to implement Learner-Centred Teaching. Future research could be conducted involving different programmes of study.